Correction: Low carbohydrate availability reduces power output at the moderate-to-heavy transition, impairs efficiency, and increases median power frequency during cycling in females - Evana Main; SangHoon Yoon; Samuel L. James; Kimberley M. Mellor; Matthew J. Brick; Warren B. Leigh; Ed Maunder (European Journal of Applied Physiology, 2026)

Low carbohydrate availability reduces power output at the moderate-to-heavy transition, impairs efficiency, and increases median power frequency during cycling in females - Evana Main; SangHoon Yoon; Samuel L. James; Kimberley M. Mellor; Matthew J. Brick; Warren B. Leigh; Ed Maunder (European Journal of Applied Physiology, 2026)
Purpose Carbohydrate availability is reduced during prolonged exercise, and this may contribute to the loss of power output at the intensity domain transitions. The aim of this study was to investigate the effects of lowered carbohydrate availability on power output at intensity domain transitions, muscle activation, and gross cycling efficiency in endurance-trained female cyclists. Methods Nine well-trained female cyclists completed a randomised, counterbalanced crossover study consisting of two conditions. Participants completed an incremental cycling test and three-minute all-out test, preceded by glycogen-depleting exercise ~ 24 h beforehand and subsequent carbohydrate ingestion of either ≥ 9 g kg −1 (HIGH) or ≤ 1 g kg −1 (LOW). Results Power output at the first ventilatory threshold was reduced in LOW (133 ± 24 vs. 152 ± 28 W, ∆ − 19 ± 14 W, P = 0.011), with no between-trial difference in power output at the lactate threshold. Gross cycling efficiency during submaximal cycling was reduced in LOW ( P = 0.003). Electromyographic median power frequency of the vastus lateralis ( P = 0.025) and vastus medialis ( P = 0.007) was higher in HIGH during submaximal cycling, with no between-trial differences in electromyographic amplitude. There was no between-trial difference in end-test power output during the three-minute all-out test. Conclusion These data suggest lowered carbohydrate availability reduced power output at the moderate-to-heavy transition, possibly due to increased recruitment of higher-threshold motor units to compensate for glycogen-depleted fibres, impairing gross cycling efficiency. These data suggest that carbohydrate availability is likely important in ‘durability’ of the moderate-to-heavy intensity transition.

Durability of the moderate-to-heavy intensity transition can be predicted using readily available markers of physiological decoupling - Jeffrey A. Rothschild; Gabriele Gallo; Kate Hamilton; Julian D. Stevenson; Harrison Dudley-Rode; Thanchanok Charoensap; Daniel J. Plews; Andrew E. Kilding; Ed Maunder (European Journal of Applied Physiology, 2025)
Purpose To assess relationships between heart rate (HR), ventilation (̇ $$\dot V$$ V ˙ E ), and respiratory frequency (F R ) decoupling and durability of the first ventilatory threshold (VT 1 ), and the strength of practical models to predict power output at VT 1 during prolonged exercise. Methods Durability of VT 1 was assessed via measurements of power output at VT 1 before and after ~ 2.5-h of initially moderate-intensity cycling in 51 trained cyclists, as part of four studies published elsewhere. In 12 of those participants, power output at VT 1 was assessed every hour until task failure. For every assessment of power output at VT 1 , HR, F R , and $$\dot V$$ V ˙ ̇ E was measured at fixed power outputs, and thus decoupling of these variables with power output was determined. Bivariate repeated-measures correlations (r rm ) between decoupling and durability of VT 1 were assessed. Multivariable models were created to predict power output at VT 1 during prolonged exercise using generalised estimating equations. Results Negative correlations were observed between exercise-induced change in power output at VT 1 and HR (r rm = −0.76, P < 0.001) and F R (r rm = −0.40, P = 0.013) decoupling, but not $$\dot V$$ V ˙ ̇ E decoupling (r rm = −0.25, P = 0.136). The final prediction model, containing baseline VT 1 and peak oxygen uptake, F R decoupling, and an interaction between HR decoupling and exercise duration, effectively predicted real-time VT 1 (mean absolute error, ~ 7.2 W; R 2 , 0.95). Conclusion HR and/or F R decoupling during controlled training sessions may be a practically useful durability assessment. Our prediction models may be an effective means of improving within-session intensity regulation and training load monitoring.

Prolonged running reduces speed at the moderate-to-heavy intensity transition without additional reductions due to increased eccentric load - Andrew M. S. Barrett; Ed Maunder (European Journal of Applied Physiology, 2025)
Aim To investigate the impact of prolonged running on speed at the moderate-to-heavy intensity transition, and whether increased eccentric load modifies exercise-induced shifts in the moderate-to-heavy intensity transition. Methods Twelve endurance-trained runners (4 females, 8 males, peak oxygen uptake 51.5 mL kg −1 min −1 in females and 56.1 mL kg −1 min −1 in males) participated. Following trials to assess speed at the first ventilatory threshold (VT 1 ) on a 0% gradient and -10% gradient, participants completed two trials: (i) level trial (LVL): 120-min of running at 0% gradient and (ii) downhill trial (DH): 120-min of running with 90-min at 0% gradient and 6 × 5-min intervals at -10% gradient (DH). Running was conducted at 90% of VT 1 speed for respective gradients. Speed at VT 1 on 0% gradient, perceived leg muscle soreness, and maximal voluntary isometric knee extensor torque were assessed pre- and post-prolonged exercise. Results An effect of time was observed for speed at VT 1 (∆-6.2 ± 3.6% in LVL and ∆-7.6 ± 3.2% in DH, P < 0.001), with no effect of condition (LVL vs. DH, P = 0.382), or time × condition interaction ( P = 0.295). Reduced metabolic energy expenditure (metabolic power) significantly contributed to the reduced speed at VT 1 in both trials ( P < 0.001), whereas changes in running economy (energetic efficiency) did not ( P = 0.228). Conclusion Prolonged moderate-intensity running reduced speed at the moderate-to-heavy intensity transition, but this was not exacerbated by increased eccentric load. Reduced speed at the moderate-to-heavy intensity transition following prolonged running was primarily attributed to decreased metabolic power.

Carbohydrate ingestion during prolonged exercise blunts the reduction in power output at the moderate-to-heavy intensity transition - Harrison Dudley-Rode; Caryn Zinn; Daniel J. Plews; Thanchanok Charoensap; Ed Maunder (European Journal of Applied Physiology, 2025)

Durability of the moderate-to-heavy-intensity transition is related to the effects of prolonged exercise on severe-intensity performance - Kate Hamilton; Andrew E. Kilding; Daniel J. Plews; Mathew J. Mildenhall; Mark Waldron; Thanchanok Charoensap; Tobias H. Cox; Matthew J. Brick; Warren B. Leigh; Ed Maunder (European Journal of Applied Physiology, 2024)
Purpose Power output at the moderate-to-heavy-intensity transition decreases during prolonged exercise, and resilience to this has been termed ‘durability’. The purpose of this study was to assess the relationship between durability and the effect of prolonged exercise on severe-intensity performance, and explore intramuscular correlates of durability. Methods On separate days, 13 well-trained cyclists and triathletes (V̇O 2 peak, 57.3 ± 4.8 mL kg −1 min −1 ; training volume, 12 ± 2.1 h week −1 ) undertook an incremental test and 5-min time trial (TT) to determine power output at the first ventilatory threshold (VT 1 ) and severe-intensity performance, with and without 150-min of prior moderate-intensity cycling. A single resting vastus lateralis microbiopsy was obtained. Results Prolonged exercise reduced power output at VT 1 (211 ± 40 vs. 198 ± 39 W, ∆ -13 ± 16 W, ∆ -6 ± 7%, P = 0.013) and 5-min TT performance (333 ± 75 vs. 302 ± 63 W, ∆ -31 ± 41 W, ∆ -9 ± 10%, P = 0.017). The reduction in 5-min TT performance was significantly associated with durability of VT 1 (r s = 0.719, P = 0.007). Durability of VT 1 was not related to vastus lateralis carnosine content, citrate synthase activity, or complex I activity ( P > 0.05). Conclusion These data provide the first direct support that durability of the moderate-to-heavy-intensity transition is an important performance parameter, as more durable athletes exhibited smaller reductions in 5-min TT performance following prolonged exercise. We did not find relationships between durability and vastus lateralis carnosine content, citrate synthase activity, or complex I activity.

Power output at the moderate-to-heavy intensity transition decreases in a non-linear fashion during prolonged exercise - Gabriele Gallo; Emanuela Luisa Faelli; Piero Ruggeri; Luca Filipas; Roberto Codella; Daniel J. Plews; Ed Maunder (European Journal of Applied Physiology, 2024)
Purpose The aims of this study were to: (i) describe the time course of the decrease in power output at the moderate-to-heavy intensity transition during prolonged exercise; (ii) investigate the association between durability of the moderate-to-heavy intensity transition and exercise capacity; and (iii) explore physiological correlates of durability of the moderate-to-heavy intensity transition. Methods Twelve trained cyclists (age: 40 ± 8 y, $$\dot{\text{V}}$$ V ˙ O 2 peak: 52.3 ± 5.2 mL·min −1 ·kg −1 ) performed an exhaustive cycling protocol involving alternating incremental exercise tests to determine power output at the moderate-to-heavy intensity transition via the first ventilatory threshold (VT 1 ), and 30-min bouts at 90% of the power output at the previously estimated VT 1 in the rested state. The individual time course of VT 1 was modelled using linear and second-order polynomial functions, and time to a 5% decrease in VT 1 (Δ5%VT 1 ) was estimated using the best-fitting model. Results Power output at VT 1 decreased according to a second-order polynomial function in 11 of 12 participants. Time-to-task failure (234 ± 66 min) was correlated with Δ5%VT 1 (139 ± 78 min, r s = 0.676, p = 0.016), and these were strongly correlated with absolute and relative rates of fat oxidation at specific exercise intensities measured during the incremental test performed in the rested state. Conclusions These data: (i) identify a non-linear time course of decreases in the moderate-to-heavy intensity transition during prolonged exercise; (ii) support the importance of durability of the moderate-to-heavy intensity transition in prolonged exercise capacity; and (iii) suggest durability of the moderate-to-heavy intensity transition is related to fat oxidation rates.

Locally applied heat stress during exercise training may promote adaptations to mitochondrial enzyme activities in skeletal muscle - Ed Maunder; Andrew King; Jeffrey A. Rothschild; Matthew J. Brick; Warren B. Leigh; Christopher P. Hedges; Troy L. Merry; Andrew E. Kilding (Pflügers Archiv - European Journal of Physiology, 2024)
There is some evidence for temperature-dependent stimulation of mitochondrial biogenesis; however, the role of elevated muscle temperature during exercise in mitochondrial adaptation to training has not been studied in humans in vivo. The purpose of this study was to determine the role of elevating muscle temperature during exercise in temperate conditions through the application of mild, local heat stress on mitochondrial adaptations to endurance training. Eight endurance-trained males undertook 3 weeks of supervised cycling training, during which mild (~ 40 °C) heat stress was applied locally to the upper-leg musculature of one leg during all training sessions (HEAT), with the contralateral leg serving as the non-heated, exercising control (CON). Vastus lateralis microbiopsies were obtained from both legs before and after the training period. Training-induced increases in complex I (fold-change, 1.24 ± 0.33 vs. 1.01 ± 0.49, P = 0.029) and II (fold-change, 1.24 ± 0.33 vs. 1.01 ± 0.49, P = 0.029) activities were significantly larger in HEAT than CON. No significant effects of training, or interactions between local heat stress application and training, were observed for complex I–V or HSP70 protein expressions. Our data provides partial evidence to support the hypothesis that elevating local muscle temperature during exercise augments training-induced adaptations to mitochondrial enzyme activity.

All models are wrong, but the critical power model is useful - Daniel Muniz-Pumares; Ed Maunder; Jon Brazier; Ben Hunter (European Journal of Applied Physiology, 2024)

Prolonged exercise shifts ventilatory parameters at the moderate-to-heavy intensity transition - Julian D. Stevenson; Andrew E. Kilding; Daniel J. Plews; Ed Maunder (European Journal of Applied Physiology, 2024)
Purpose To quantify the effects of prolonged cycling on the rate of ventilation ( $${\dot{\text{V}}}_{{\text{E}}}$$ V ˙ E ), frequency of respiration (F R ), and tidal volume (V T ) associated with the moderate-to-heavy intensity transition. Methods Fourteen endurance-trained cyclists and triathletes (one female) completed an assessment of the moderate-to-heavy intensity transition, determined as the first ventilatory threshold (VT 1 ), before (PRE) and after (POST) two hours of moderate-intensity cycling. The power output, $${\dot{\text{V}}}_{{\text{E}}}$$ V ˙ E , F R , and V T associated with VT 1 were determined PRE and POST. Results As previously reported, power output at VT 1 significantly decreased by ~ 10% from PRE to POST. The $${\dot{\text{V}}}_{{\text{E}}}$$ V ˙ E associated with VT 1 was unchanged from PRE to POST (72 ± 12 vs. 69 ± 13 L . min −1 , ∆ − 3 ± 5 L . min −1 , ∆ − 4 ± 8%, P = 0.075), and relatively consistent (within-subject coefficient of variation, 5.4% [3.7, 8.0%]). The $${\dot{\text{V}}}_{{\text{E}}}$$ V ˙ E associated with VT 1 was produced with increased F R (27.6 ± 5.8 vs. 31.9 ± 6.5 breaths . min −1 , ∆ 4.3 ± 3.1 breaths . min −1 , ∆ 16 ± 11%, P = 0.0002) and decreased V T (2.62 ± 0.43 vs. 2.19 ± 0.36 L . breath −1 , ∆ − 0.44 ± 0.22 L . breath −1 , ∆ − 16 ± 7%, P = 0.0002) in POST. Conclusion These data suggest prolonged exercise shifts ventilatory parameters at the moderate-to-heavy intensity transition, but $${\dot{\text{V}}}_{{\text{E}}}$$ V ˙ E remains stable. Real-time monitoring of $${\dot{\text{V}}}_{{\text{E}}}$$ V ˙ E may be a useful means of assessing proximity to the moderate-to-heavy intensity transition during prolonged exercise and is worthy of further research.

Skeletal muscle proteins involved in fatty acid transport influence fatty acid oxidation rates observed during exercise - Ed Maunder; Jeffrey A. Rothschild; Andreas M. Fritzen; Andreas B. Jordy; Bente Kiens; Matthew J. Brick; Warren B. Leigh; Wee-Leong Chang; Andrew E. Kilding (Pflügers Archiv - European Journal of Physiology, 2023)
Several proteins are implicated in transmembrane fatty acid transport. The purpose of this study was to quantify the variation in fatty acid oxidation rates during exercise explained by skeletal muscle proteins involved in fatty acid transport. Seventeen endurance-trained males underwent a (i) fasted, incremental cycling test to estimate peak whole-body fatty acid oxidation rate (PFO), (ii) resting vastus lateralis microbiopsy, and (iii) 2 h of fed-state, moderate-intensity cycling to estimate whole-body fatty acid oxidation during fed-state exercise (FO). Bivariate correlations and stepwise linear regression models of PFO and FO during 0–30 min (early FO) and 90–120 min (late FO) of continuous cycling were constructed using muscle data. To assess the causal role of transmembrane fatty acid transport in fatty acid oxidation rates during exercise, we measured fatty acid oxidation during in vivo exercise and ex vivo contractions in wild-type and CD36 knock-out mice. We observed a novel, positive association between vastus lateralis FATP1 and PFO and replicated work reporting a positive association between FABPpm and PFO. The stepwise linear regression model of PFO retained CD36, FATP1, FATP4, and FABPpm, explaining ~87% of the variation. Models of early and late FO explained ~61 and ~65% of the variation, respectively. FATP1 and FATP4 emerged as contributors to models of PFO and FO. Mice lacking CD36 had impaired whole-body and muscle fatty acid oxidation during exercise and muscle contractions, respectively. These data suggest that substantial variation in fatty acid oxidation rates during exercise can be explained by skeletal muscle proteins involved in fatty acid transport.

Carbohydrate, but not fat, oxidation is reduced during moderate-intensity exercise performed in 33 vs. 18 °C at matched heart rates - Thanchanok Charoensap; Andrew E. Kilding; Ed Maunder (European Journal of Applied Physiology, 2023)
Purpose Exposure to environmental heat stress increases carbohydrate oxidation and extracellular heat shock protein 70 (HSP70) concentrations during endurance exercise at matched absolute, external work rates. However, a reduction in absolute work rate typically occurs when unacclimated endurance athletes train and/or compete in hot environments. We sought to determine the effect of environmental heat stress on carbohydrate oxidation rates and plasma HSP70 expression during exercise at matched heart rates (HR). Methods Ten endurance-trained, male cyclists performed two experimental trials in an acute, randomised, counterbalanced cross-over design. Each trial involved a 90-min bout of cycling exercise at 95% of the HR associated with the first ventilatory threshold in either 18 (TEMP) or 33 °C (HEAT), with ~ 60% relative humidity. Results Mean power output (17 ± 11%, P < 0.001) and whole-body energy expenditure (14 ± 8%, P < 0.001) were significantly lower in HEAT. Whole-body carbohydrate oxidation rates were significantly lower in HEAT (19 ± 11%, P = 0.002), while fat oxidation rates were not different between-trials. The heat stress-induced reduction in carbohydrate oxidation was associated with the observed reduction in power output (r = 0.64, 95% CI, 0.01, 0.91, P = 0.05) and augmented sweat rates (r = 0.85, 95% CI, 0.49, 0.96, P = 0.002). Plasma HSP70 and adrenaline concentrations were not increased with exercise in either environment. Conclusion These data contribute to our understanding of how moderate environmental heat stress is likely to influence substrate oxidation and plasma HSP70 expression in an ecologically-valid model of endurance exercise.

Prolonged cycling reduces power output at the moderate-to-heavy intensity transition - Julian D. Stevenson; Andrew E. Kilding; Daniel J. Plews; Ed Maunder (European Journal of Applied Physiology, 2022)
Purpose To determine the effect of prolonged exercise on moderate-to-heavy intensity transition power output and heart rate. Methods Fourteen endurance-trained cyclists and triathletes took part in the present investigation (13 males, 1 female, V·O 2 peak 59.9 ± 6.8 mL . kg −1. min −1 ). Following a characterisation trial, participants undertook a five-stage incremental step test to determine the power output and heart rate at the moderate-to-heavy intensity transition before and after two hours of cycling at 90% of the estimated power output at first ventilatory threshold (VT 1 ). Results Power output at the moderate-to-heavy intensity transition significantly decreased following acute prolonged exercise when determined using expired gases (VT 1 , 217 ± 42 W vs. 196 ± 42 W, P < 0.0001) and blood lactate concentrations (LoglogLT, 212 ± 47 W vs. 190 ± 47 W, P = 0.004). This was attributable to loss of efficiency (VT 1 , -8 ± 10 W; LoglogLT, − 7 ± 9 W) and rates of metabolic energy expenditure at the transition (VT 1 , − 14 ± 11 W; LoglogLT, − 15 ± 22 W). The heart rate associated with the moderate-to-heavy intensity transition increased following acute prolonged exercise (VT 1, 142 ± 9 beats . min −1 vs. 151 ± 12 beats . min −1 , P < 0.001; LoglogLT, 140 ± 13 beats . min −1 vs. 150 ± 15 beats . min −1 , P = 0.006). Conclusion These results demonstrate the external work output at the moderate-to-heavy intensity transition decreases during prolonged exercise due to decreased efficiency and rates of metabolic energy expenditure, but the associated heart rate increases. Therefore, individual assessments of athlete ‘durability’ are warranted.

A three-minute all-out test performed in a remote setting does not provide a valid estimate of the maximum metabolic steady state - Ed Maunder; Jeffrey A. Rothschild; Andrius Ramonas; Matthieu Delcourt; Andrew E. Kilding (European Journal of Applied Physiology, 2022)
Purpose The three-minute all-out test (3MT), when performed on a laboratory ergometer in a linear mode, can be used to estimate the heavy–severe-intensity transition, or maximum metabolic steady state (MMSS), using the end-test power output. As the 3MT only requires accurate measurement of power output and time, it is possible the 3MT could be used in remote settings using personal equipment without supervision for quantification of MMSS. Methods The aim of the present investigation was to determine the reliability and validity of remotely performed 3MTs (3MT R ) for estimation of MMSS. Accordingly, 53 trained cyclists and triathletes were recruited to perform one familiarisation and two experimental 3MT R trials to determine its reliability. A sub-group ( N = 10) was recruited to perform three-to-five 30 min laboratory-based constant-work rate trials following completion of one familiarisation and two experimental 3MT R trials. Expired gases were collected throughout constant-work rate trials and blood lactate concentration was measured at 10 and 30 min to determine the highest power output at which steady-state $${{\dot{V}O}}_{2}$$ V ˙ O 2 (MMSS- $${{\dot{V}O}}_{2}$$ V ˙ O 2 ) and blood lactate (MMSS-[La − ]) were achieved. Results The 3MT R end-test power (EP remote ) was reliable (coefficient of variation, 4.5% [95% confidence limits, 3.7, 5.5%]), but overestimated MMSS (EP remote , 283 ± 51 W; MMSS- $${{\dot{V}O}}_{2}$$ V ˙ O 2 , 241 ± 46 W, P = 0.0003; MMSS-[La − ], 237 ± 47 W, P = 0.0003). This may have been due to failure to deplete the finite work capacity above MMSS during the 3MT R . Conclusion These results suggest that the 3MT R should not be used to estimate MMSS in endurance-trained cyclists.

Peak fat oxidation is positively associated with vastus lateralis CD36 content, fed-state exercise fat oxidation, and endurance performance in trained males - Ed Maunder; Daniel J. Plews; Gareth A. Wallis; Matthew J. Brick; Warren B. Leigh; Wee-Leong Chang; Tom Stewart; Casey M. Watkins; Andrew E. Kilding (European Journal of Applied Physiology, 2022)